Indigenous Islam and Puritan Islam in Indonesia through Nasr Hamid Abu Zayd's Hermeneutic Studies - Soedrajad, Mochammad Rijaal; Tohir, Naupal Asnawi (JURNAL ISLAM NUSANTARA, 2022)
This paper studies the essence of Islam in the discourse ofÂ  Puritan Islam and Indigenous Islam in Indonesia. The Muslim community in Indonesia is now fragmented into two distinct groups. The first group considers that the essence of Islam must follow Middle Eastern traditions in all its aspects. The second group considers that the essence of Islam must adapt to local traditions/cultures as long as it does not conflict with the holy text of the Qur'anQur'an and Sunnah of Muhammad SAW. The purpose of this research is to explore what the essence of Islam in Indonesia should be. The method used in this paper is a literature study through Nasr HamidÂ  Abu Zayd's hermeneutic approach with his ideas related to the reading of the Qur'an through the historical context and criticism of Quranic verses. The results of the study indicate that the essence of Indonesian Islam is Indigenous Islam because Islam should be able to synergize with all times and places and thus be able to have a dialectic with the plurality of culture and society so that Islam can be accepted by all, including Indonesian cultures that is different from the Middle Eastern culture.